Character Value In The Story Of Bawang Merah Bawang Putih and Their Relevance For Strengthening Character Of Elementary School Students: Nilai-Nilai Karakter Dalam Dongeng “Bawang Merah Bawang Putih” dan Relevansinya Untuk Penguatan Karakter Siswa Sekolah Dasar - Aliefa Rahmadewi; Supriyadi Supriyadi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the values ​​of character education in the fairy tale Bawang Merah Bawang Putih and its relevance for strengthening the character of elementary school students. The data of this research is the story of Bawang Merah Bawang Putih which was obtained from the fairy tale book by Runna Aulia and Ghais Ramadhani. The data collection technique used is documentation. This stage of the data analysis technique is carried out by data condensation. Presentation of data, as well as conclusions and verification of research results. The results of this study are 5 character values ​​contained in the fairy tale Bawang Merah Bawang Putih, such as the value of the character of hard work, the value of the character of discipline, the value of the character of responsibility, the value of the character of social care, the value of the character of curiosity. This study also found 5 character values ​​that exist in strengthening character education, such as the value of telligiosity, nationalism, integrity, independence and mutual cooperation. The characters in this fairy tale can also be used as learning content at school. there are good examples so that students can find good learning to be applied to everyday life such as the school environment, community and family environment.